Pengaruh Komunikasi Administrasi dan Motivasi Kerja Pegawai Terhadap Kualitas Pelayanan pada Kantor Kecamatan Salahutu Kabupaten Maluku Tengah - Tuarita, Normalina; Rengifurwarin, Zainal Abidin; Bahasoan, Aminah (Jurnal Ilmiah Global Education, 2025)
This study aims to analyze the influence of administrative communication and work motivation on service quality at the Salahutu District Office, Central Maluku Regency. The research employed a quantitative survey approach, collecting data through questionnaires distributed to all office employees. Data analysis was performed using multiple linear regression, t-test, F-test, and the coefficient of determination (R²) to examine both partial and simultaneous effects of independent variables on the dependent variable. The results indicate that administrative communication has a positive and significant effect on service quality, with a regression coefficient of 0.539 and Beta value of 0.651, demonstrating the dominant role of communication in influencing service quality. Conversely, work motivation does not have a significant partial effect, although its influence is positive. Simultaneously, administrative communication and work motivation together significantly affect service quality with a significance level of < 0.001. These findings highlight the importance of synergy between effective internal communication and employee motivation in improving public service performance. The study provides practical implications for the Salahutu District Office management to enhance communication training, optimize digital media, promote a democratic communication culture, and increase employee motivation through rewards and adequate work facilities.